2001
DOI: 10.1074/jbc.m104185200
|View full text |Cite
|
Sign up to set email alerts
|

δEF1 Binds to a Far Upstream Sequence of the Mouse Pro-α1(I) Collagen Gene and Represses Its Expression in Osteoblasts

Abstract: The transcription of type I collagen genes is tightly regulated, but few cis-acting elements have been identified that can modulate the levels of expression of these genes. Generation of transgenic mice harboring various segments of the mouse pro-␣1(I) collagen promoter led us to suspect that a repressor element was located between ؊10.5 and ؊17 kilobase pairs. Stable and transient transfection experiments in ROS17/2.8 osteoblastic cells confirmed the existence of such a repressor element at about ؊14 kilobase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
(28 reference statements)
3
38
1
Order By: Relevance
“…It is known that ZEB1 contributes to maintaining the cell cycle because ZEB1 antisense RNA abrogates proliferation (24), apparently due to regulation of the p73 gene in muscle and neuronal cells (6,25). It is frequently observed that ZEB1 represses genes that are markers of terminal differentiation in skeletal muscle (10,12) and represses a1-collagen and collagen type II genes in osteoblasts (22,23) and vascular smooth muscle cells (26). ZEB1 has been suggested to function as a repressor of skeletal muscle differentiation based on the repression of myogenesis in cell lines in vitro (10-12); however, in vivo, it is highly expressed in actively differentiating myoblasts and myofibers (6) and there is no skeletal muscle defect in ZEB1-null embryos (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ZEB1 contributes to maintaining the cell cycle because ZEB1 antisense RNA abrogates proliferation (24), apparently due to regulation of the p73 gene in muscle and neuronal cells (6,25). It is frequently observed that ZEB1 represses genes that are markers of terminal differentiation in skeletal muscle (10,12) and represses a1-collagen and collagen type II genes in osteoblasts (22,23) and vascular smooth muscle cells (26). ZEB1 has been suggested to function as a repressor of skeletal muscle differentiation based on the repression of myogenesis in cell lines in vitro (10-12); however, in vivo, it is highly expressed in actively differentiating myoblasts and myofibers (6) and there is no skeletal muscle defect in ZEB1-null embryos (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to roles in lymphopoiesis (21) and skeletal patterning (17), ZEB1 is likely involved in chondrogenesis (22,23), neurogenesis, neural crest cell development (24), and tumorigenesis (13)(14)(15). Some of these roles seem to involve regulation of events at the crossroad between proliferation and differentiation (6,24).…”
Section: Discussionmentioning
confidence: 99%
“…A number of GC-rich TATA-less promoters regulated by Sp1 and Sp3 have previously been shown to contain sequence elements that confer tissue-specific expression (33,34). Additionally, the CBS 5Ј-flanking sequence contains numerous binding sites for delta EF1 and HNF-3 beta, which have previously been shown to regulate gene expression in a tissue-specific manner (35,36). Although our investigation of the Ϫ1b basal promoter indicated that the proximal 5 kbp of 5Ј-flanking sequence neither significantly enhances nor represses CBS Ϫ1b promoter activity in HepG2 cells, it is possible that this region contains sequence elements that act to repress promoter activity in CBS-deficient tissues.…”
Section: Figmentioning
confidence: 99%
“…For instance in developing mesodermal and neural tissues, ZEB1 levels change dynamically during differentiation. 4,5 It is involved in lymphopoiesis, 6 skeletal patterning, 7 chondrogenesis, 8,9 neurogenesis, and neural crest cell development. 10 More recently, a role for ZEB1 in tumor progression, particularly in epithelial to mesenchymal transition (EMT), has been reported, as reviewed by Peinado et al…”
mentioning
confidence: 99%